Histopathological and Molecular Investigation of Pasteurella multocida Specific Outbreak in a Sheep Flock with High Mortality in Egypt - Eman B., Abd-Elfatah; Marwa B, Salman; Asmaa I, Zin Eldin; Emam, Mahmoud (The Iraqi Journal of Veterinary Medicine, 2025)
Pasteurella is a major bacterial pathogen causing respiratory signs due to pneumonia and septicemia that usually affects young animals and humans, leading to significant economic losses. it is responsible for highly contagious infections in animals, leading to high mortality and consequently financial losses for the breeders. The aim of the study was the rapid detection of Pasteurella infection outbreak. This study examined a specific outbreak of pasteurellosis in a sheep flock in Egypt based on clinical and postmortem diagnoses, molecular detection using universal and specific primers, as well as the histopathological examination to demonstrate the pathological changes on internal organs. The results revealed that 15 of 70 animals (21.4%)—primarily lambs under one year—died suddenly with mild respiratory signs. Postmortem examination revealed congested, consolidated lungs and liver lesions. Bacteriological culturing showed characteristic non-hemolytic colonies on the blood agar, and the Gram’s staining confirmed bipolar coccobacilli. PCR targeting the 16S rRNA gene and SYBR Green real-time PCR targeting the KMT1 gene identified Pasteurella multocida (P. multocida) in 8/10 samples. Septicemic bronchopneumonia and hepatic degeneration highlight the importance of histopathological investigation align with molecular assays for accurate diagnosis of P. multocida infection in sheep